Bovine herpesviruses induce different cell death forms in neuronal and glial-derived tumor cell cultures - Cardoso, Tereza C. [UNESP]; Rosa, Ana Carolina G. [UNESP]; Ferreira, Helena L.; Okamura, Lucas H. [UNESP]; Oliveira, Bruna R. S. M. [UNESP]; Vieira, Flavia V. [UNESP]; Silva-Frade, Camila [UNESP]; Gameiro, Roberto [UNESP]; Flores, Eduardo F. (Springer, 2016)
Oncolytic viruses have the ability to infect tumor cells and leave healthy cells intact. In this study, bovine herpesvirus 1 (BHV1; Los Angeles, Cooper, and SV56/90 strains) and bovine herpesvirus 5 (BHV5; SV507/99 and GU9457818 strains) were used to infect two neuronal tumor cell lineages: neuro2a (mouse neuroblastoma cells) and C6 (rat glial cells). BHV1 and BHV5 strains infected both cell lines and positively correlated with viral antigen detection (p < 0.005). When neuro2a cells were infected by Los Angeles, SV507/99, and GU9457818 strains, 40 % of infected cells were under early apoptosis and necroptosis pathways. Infected C6 cells were > 40 % in necroptosis phase when infected by BHV5 (GU9457818 strain). Blocking caspase activation did not interfere with cell death. However, when necroptosis was blocked, 60-80 % of both infected cells with either virus switched to early apoptosis pathway with no interference with virus replication. Moreover, reactive oxygen species production and mitochondrial membrane dysfunction were detected at high levels in both infected cell lines. In spite of apoptosis and necroptosis blockage, tumor necrosis factor alpha (TNFA) and virus transcription were positively correlated for all viral strains studied. Thus, these results contribute to the characterization of BHV1 and BHV5 as potential oncolytic viruses for non-human cells. Nonetheless, the mechanisms underlying their oncolytic activity in human cells are still to be determined.
Keywords: Oncolytic viruses; Animal herpesvirus; Apoptosis; Necroptosis; Oxidative stress; Pathogenesis